2013
DOI: 10.1016/j.bbadis.2012.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of wound healing and organ fibrosis by toll-like receptors

Abstract: Chronic injury often triggers maladaptive wound healing responses leading to the development of tissue fibrosis and subsequent organ malfunction. Inflammation is a key component of the wound healing process and promotes the development of organ fibrosis. Here, we review the contribution of Toll-like receptors (TLRs) to wound healing with a particular focus on their role in liver, lung, kidney, skin and myocardial fibrosis. We discuss the role of TLRs on distinct cell populations that participate in the repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 227 publications
(229 reference statements)
2
103
0
1
Order By: Relevance
“…Chronic liver diseases are associated with enhanced portal inflow of gut-derived microbiota products [lipopolysaccharide (LPS), bacterial DNA, peptidoglycan, viral and fungal components host DNA], due to increased intestinal permeability (29). Several studies have reported the beneficial impact of intestinal decontamination by antibiotics on liver fibrogenesis, suggesting that gut microbiota enhances liver fibrogenesis (79).…”
Section: Immunoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic liver diseases are associated with enhanced portal inflow of gut-derived microbiota products [lipopolysaccharide (LPS), bacterial DNA, peptidoglycan, viral and fungal components host DNA], due to increased intestinal permeability (29). Several studies have reported the beneficial impact of intestinal decontamination by antibiotics on liver fibrogenesis, suggesting that gut microbiota enhances liver fibrogenesis (79).…”
Section: Immunoregulationmentioning
confidence: 99%
“…The identification of Toll-like receptors (TLRs) in HSCs has uncovered the major contribution of gut-derived bacterial products in the inflammatory reaction underlying progression of fibrosis (29). Chronic liver diseases are associated with enhanced portal inflow of gut-derived microbiota products [lipopolysaccharide (LPS), bacterial DNA, peptidoglycan, viral and fungal components host DNA], due to increased intestinal permeability (29).…”
Section: Immunoregulationmentioning
confidence: 99%
“…Necrotic cell supernatants were prepared from mouse tubular cells by repeated freezing and thawing. BMDCs were stimulated with necrotic supernatant with different concentration (50,150, and 250 ml) as well as AhR agonist (FICZ; Enzo Life Sciences) and H 2 O 2 (Merck). We purchased ultrapure LPS (from Escherichia coli strain K12), pI:C RNA, Pam3Cys, imiquimod, and CpG (InvivoGen).…”
Section: Bmdc Stimulation Experimentsmentioning
confidence: 99%
“…In addition to PDGF and TGF-β, a number of other mediators such as angiotensin II, endothelin-1, chemokines, leptin, interleukin-4 (IL-4), IL-6 and IL-13 play vital roles in fibrogenesis (13). Despite their protuberant role in fibrogenesis, recent studies indicate Toll-like receptors (TLRs), a group of receptors that regulate innate and adaptive immune responses, as significant modulators of inflammation during fibrosis (14)(15)(16). TLRs recognize pathogen-associated molecular patterns (PAMPs) and activate innate and adaptive immune responses to confiscate pathogens.…”
Section: Cellular Crosstalk Mechanism Of Toll-like Receptors In Gingimentioning
confidence: 99%